Psychological factors as predictors of readiness to combat crime among police officers in Osun State Command, Nigeria - Ayinde, Adeboye Titus (International journal of police science & management, 2018)
The increasing crime rate and apparent reduction in combatting crime by law enforcement agencies in Nigeria, particularly the Nigerian Police, deserve attention from a psychological point of view. This study examined the extent to which locus of control and emotional intelligence (EI) predict readiness to combat crime among police officers in Osun State Police Command, Nigeria. The study used primary data embedded in a descriptive survey design. A multistage sampling technique was adopted to obtain data from the sample population. Three police area commands in Osun State, namely Osogbo, Ile-Ife and Ilesa, were selected for the study. The sample comprised 258 police officers selected using a stratified random technique with different units of command as the basis of stratification. Three instruments, the Work Locus of Control Scale, Brief Emotional Intelligence Scale and Readiness to Combat Crime Scale were used. Data were analysed using descriptive (percentage count) and inferential statistics (linear regression and t-test). The results showed that locus of control did not significantly predict readiness to combat crime among police officers in Osun State Command [F(1,214) = 0.371; p > 0.05], whereas EI [F(1,225) = 131.045; p < 0.05] did. The study concluded that EI successfully predicted readiness to combat crime among police officers in Osun State Command, whereas locus of control had no influence.